Pemanfaatan Limbah Sayuran Busuk terhadap Pertumbuhan Tanaman Sawi (Brassica juncea L) - Fadilla Roji; Abdul Hasym Mazhurin Siregar; Rizka Lucy Nadia; Indaya Febriani Tanjung (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research was conducted in the courtyard of Lau Dendang Village, Medan, North Sumatra. Which is carried out from October to November. This research was conducted to study the manufacture of compost using the vermicomposting method which utilizes organic waste such as rotting vegetables and to determine differences in growth rates from applying compost and water to mustard greens. The results of this study indicate that the application of compost from rotting vegetable waste has an impact on mustard plants which produce stem height, number of leaves and leaf width, in the application of water the resulting impact also develops well, but not as well as in the application of compost fertilizer. So it can be concluded that the application of compost has more influence on the rate of growth and development of mustard greens because it can increase the fertility in the soil. Keywords: Fertilizer, Vegetables, Planting